1991
DOI: 10.1002/j.1460-2075.1991.tb04978.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing human tumour necrosis factor: a predictive genetic model of arthritis.

Abstract: We have generated transgenic mouse lines carrying and expressing wild‐type and 3′‐modified human tumour necrosis factor (hTNF‐alpha, cachectin) transgenes. We show that correct, endotoxin‐responsive and macrophage‐specific hTNF gene expression can be established in transgenic mice and we present evidence that the 3′‐region of the hTNF gene may be involved in macrophage‐specific transcription. Transgenic mice carrying 3′‐modified hTNF transgenes shows deregulated patterns of expression and interestingly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
1,124
1
30

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,472 publications
(1,189 citation statements)
references
References 47 publications
28
1,124
1
30
Order By: Relevance
“…Earlier studies with TNF-deficient animals demonstrated the critical role of TNF in mediating anti-bacterial host defenses and supporting development of secondary lymphoid organ structure and function [31,42]. In further studies, Tg overexpression of TNF revealed its crucial involvement in the pathogenesis of arthritis [52] and Crohn's-like inflammatory bowel disease [53]. With reference to autoimmune disease pathogenesis, in various animal models of autoimmunity, the role of TNF is shown to be both proinflammatory and immuneor disease-suppressive [34].…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies with TNF-deficient animals demonstrated the critical role of TNF in mediating anti-bacterial host defenses and supporting development of secondary lymphoid organ structure and function [31,42]. In further studies, Tg overexpression of TNF revealed its crucial involvement in the pathogenesis of arthritis [52] and Crohn's-like inflammatory bowel disease [53]. With reference to autoimmune disease pathogenesis, in various animal models of autoimmunity, the role of TNF is shown to be both proinflammatory and immuneor disease-suppressive [34].…”
Section: Discussionmentioning
confidence: 96%
“…Inhibition of RANKL via OPG at the time of disease onset can prevent bone erosion (18). In addition, in a model of TNF␣-induced arthritis, OPG treatment is beneficial in terms of cartilage destruction, without affecting inflammation (60,61). Moreover, osteoclast numbers have been found to be significantly reduced in animals treated with OPG.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Moreover, osteoclast numbers have been found to be significantly reduced in animals treated with OPG. Therefore, the TNF␣-triggered joint destruction is dependent on the expression of RANKL, and OPG seems to be an effective therapeutic tool for the prevention of TNF␣-mediated destruction (61,62).…”
Section: Animal Modelsmentioning
confidence: 99%
“…TNF was implicated in the pathogenesis of a localized autoimmune disease with the demonstration that transgenic mice expressing human TNF coupled to the 3 0 untranslated region of b globin developed a striking polyarthritis. 2 TNF knockout mice showed that TNF is essential in resistance to infectious disease. 3 That these findings were relevant to human autoimmune/inflammatory diseases is evidenced by the high efficacy of anti-TNF antibodies (Infliximab) and recombinant soluble chimeric receptor in treating rheumatoid arthritis (RA) and Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%